A Lived Experience of Mothers’ Perspectives on Their Children’s Use of Digital Technology: A Phenomenological Study - Maharjan, Gayatri; Uprety, Durga (Rupantaran: A Multidisciplinary Journal, 2025)
Digital technology, firmly entrenched in the rapidly evolving and diverse landscape of the 21st century, has become an integral part of our lives. This Phenomenological study aims to explore the faced challenges and benefits that mothers associate with their children's engagement in digital technology and screen used. It focuses on understanding the lived experiences of mothers in navigating their children's engagement with digital technology. This study delves into the multifaceted challenges and opportunities that mothers encounter as they bridge the gap between their children's digital world and the physical realm. It explores the ways in which mothers perceive and manage the impact of digital technology on their children's well-being, education, and social development. In an era marked by virtual connectivity and the digitalization of education, mothers' insights are invaluable in shaping effective parenting strategies and promoting healthy digital habits among children. Result of study reveal two major themes; parenting in digital era and learning from the globe. The conclusion of the study highlights the importance of balancing children's digital technology use time, maintaining open communication, setting clear boundaries, being aware of screen time and, encouraging outdoor plays as critical components of effective parenting process. This study focused on empowering mothers with knowledge and resources to navigate the complexities of the digital age while fostering meaningful connections within the family, enhancing socialization and improving the parenting process.